Anti-Hyperuricemic and Xanthine Oxidase Inhibitory Effects of Pogostemon cablin (Blanco) Benth. - Bui Thanh Tung*; Do Thi Hong Khanh; Nguyen Thi Thuy; Trinh Mai Phuong; Nguyen Thi Minh Anh (Iranian Society of Pharmacognosy, 2023)
Background and objectives: Hyperuricemia is one of the major causes of gout and other oxidative stress-related diseases. Inhibition of xanthine oxidase activity, an enzyme that converts hypoxanthine to uric acid, has been considered as one of the therapeutic methods for hyperuricemia. Pogostemon cablin (Blanco) Benth. has been widely used in traditional medicine in Asia. This study aimed to evaluate the anti-hyperuricemic and xanthine oxidase inhibitory effect of extracts and fractions of Pogostemon cablin. Methods: The dried aerial parts of P. cablin were soaked in 70% ethanol at room temperature for 72 h and were successively fractionated with n-hexane, ethyl acetate and n-butanol. Xanthine oxidase inhibitory activity of the samples was determined spectrophotometrically at 290 nm.  The hypouricemic effect of extract was investigated in normal and hyperuricemic mice induced by potassium oxonate. Results: Our results showed that the ethyl acetate fraction of P. cablin was able to inhibit xanthine oxidase with IC50 value of 96.39 ± 2.56 µg/mL. Moreover, P. cablin ethanol extract was found to reduce blood uric acid in Swiss albino mice at doses of 100 and 300 mg/kg and increased renal excretion of uric acid. Conclusion:Pogostemon cablin and extracts and fractions may have the potential to prevent hyperuricemia and require further clinical research.